The Relationship Of Nutritional Status To Pediatric Learning Achievement In Primary School-Age Children - Tagha Ichwan Maulana; Rahman, Aam Ali; Mulyanto, Respaty (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Nutritional status is a measure of an individual's body condition, which can be observed through the food consumed and the utilization of nutrients. This research aims to determine the correlation between nutritional status and learning achievement in elementary school students in Cirebon Regency. This study employed a correlational research design. Purposive sampling was used to select 30 students aged 9-12 years old as the sample. The instruments used in this study were the CDC growth chart and the student's physical education report card scores for the odd semester of the 2023-2024 academic year. Data analysis was performed using Pearson correlation analysis with the help of SPSS 20 software. The normality test results showed that the data for nutritional status (p-value = 0.100) and physical education learning achievement (p-value = 0.095) were normally distributed. The linearity test showed a p-value of 0.802, indicating a linear relationship between the variables. The Pearson product-moment correlation test yielded a significance value (2-tailed) of 0.474 and a correlation coefficient (r) of 0.361. Since the p-value was greater than 0.05 and the r-value was greater than 0.05, it can be concluded that there is a significant correlation between nutritional status and learning achievement, indicating that nutritional status has a moderate effect on learning achievement.